Sycacantha Diakonoff, 1959 from China, with the descriptions of three new species (Lepidoptera: Tortricidae: Olethreutinae) - Feng, Weixing; Zhuang, Jialiang; Yu, Haili (Zootaxa, 2019)
Nine species of Sycacantha Diakonoff, 1959 are recorded from China. Among them, three are described as new: S. typicusivalva, sp. nov., S. camerata, sp. nov., and S. decursiva, sp. nov. Two new combinations are proposed based on DNA barcodes and characters of the male genitalia: S. diserta (Meyrick, 1909), comb. nov., and Phaecasiophora obtundana (Kuznetzov, 1988), comb. nov. Sycacantha complicitana (Walker, 1863) and S. catharia Diakonoff, 1973 are newly recorded from China. Photographs of adults and genitalia of the new species and new combinations are provided, and a key to the species based on genitalia is given.